What motivates Ugandan NGOs to diversify: Risk reduction or private gain? - Canh Thien Dang; Trudy Owens (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2017)
We examine the motives that shape an NGO's decision to diversify the activities it undertakes. We identify two primary motivations, namely the aim to reduce idiosyncratic risks related to future funding and the desire to gain private benefits. We incorporate both in a theoretical framework and derive predictions regarding how an NGO responds to a change in incentives offered by their stakeholders. We predict that under an endogenous incentive scheme, the reaction of the agent will depend on the relative magnitude of the two motivators. We exploit the 2007 historic flood in Uganda and the surge in the international aid to affected areas to examine how Ugandan NGOs change their diversification behaviour following the change in incentives from contractual funding. We find diversification is negatively related to financial incentives from stakeholders. Combining with our theoretical predictions, the result suggests that NGOs diversify mainly to reduce risks rather than to capture private gains, including ability signalling, prestige, career concerns or altruism. Policies targeting financial stability for grassroots NGOs are highly recommended.
Keywords: L25; L31; 330; NGOs; diversification; risk aversions; motivations; historic flood